Joint associations of parental personality traits and socio‐economic position with trajectories of offspring depression: Findings from up to 6925 families in a UK birth cohort. Issue 3 (22nd August 2021) - Cadman, Tim; Kwong, Alex S. F.; Moran, Paul; O'Mahen, Heather; Culpin, Iryna; Lawlor, Deborah A.; Pearson, Rebecca M.
Abstract: Background: Parental personality may influence the course of offspring depression but epidemiological evidence for associations is lacking. It is also unknown whether associations between parental personality and offspring depression differ by socio‐economic position (SEP). Our aims were to describe the trajectories of depressive symptoms across adolescence of offspring of parents with and without maladaptive personality traits and to test for effect modification by SEP. Methods: A longitudinal study in the Avon Longitudinal Study of Parents and Children birth cohort ( n s = 3054–7046). Exposures were binary measures of maladaptive maternal and paternal personality traits. The outcome was depressive symptoms measured over nine occasions (ages 11–24) using the short mood and feelings questionnaire (SMFQ; range: 0–26). Effect modifiers were parental education and self‐reported material hardship. Multilevel growth curve models were used to estimate trajectories. Results: offspring of mothers with high (vs. low) maladaptive traits showed higher levels of depressive symptoms at multiple ages of adolescence, the greatest of which was observed at age 22 (predicted SMFQ difference age 10 = 0.66, 95% confidence intervals [CIs]: 0.25 to 1.28; age 22 = 1.00, CI: 0.51 to 1.50). There was weaker and inconsistent evidence of an association between paternal maladaptive personality and offspring depressive symptoms (SMFQ difference age 10 = 0.21, CI: −0.58 to 0.99; age 22 = 0.02, CI: −0.94 to 0.90). Lower SEP was also associated with higher offspring depressive symptoms (SMFQ difference material hardship vs. no hardship age 10 = 0.79, 95% CI: 0.46 to 1.13; age 22 = 0.96, CI: 0.56 to 1.36). There was minimal statistical evidence for effect modification. Conclusions: The offspring of mothers with high levels of maladaptive personality traits show evidence of greater depressive symptoms throughout adolescence although the absolute increase in symptoms is small. Evidence for the associations with fathers' personality was weaker. Socio‐economic position and maladaptive personality traits appear to be independent risk factors for offspring depressive symptoms.